The Government's Internal Control System and Financial Performance Supervision Mechanism - Victor Cornelis; Theofilus J.F.K Matrutty; Ashwin Siahainenia; Albertus Lalaun (Pusat Riset dan Inovasi Nasional, 2024)
The study uses a quantitative approach to determine whether the effectiveness of internal control functions affects the financial performance of the Ambon City Government. Primary data used. All Ambon City Government employees are included in this research population. Purposive sampling consisted of 63 individuals. Data is collected through the dissemination of questionnaires and analyzed using simple linear regression analysis. The results of this study show that the financial performance of the Ambon City government is strongly influenced by the performance of internal control functions.